Effects of firewood harvesting intensity on biodiversity and ecosystem services in shrublands of northern Patagonia - Matías G. Goldenberg; Facundo J. Oddi; Juan H. Gowda; Lucas A. Garibaldi (Forest Ecosystems, 2020)
Abstract Background Forest management has historically focused on provisioning of goods (e.g. timber, biomass), but there is an increasing interest to manage forests also to maintain biodiversity and to provide other ecosystem services (ES). Methods We evaluated the effects of firewood harvesting intensity on biodiversity and different ES in three contrasting shrubland sites in northern Patagonia (Argentina). At each site, four harvesting treatments, representing various levels of harvest intensity, were randomly assigned to eight permanent sample plots of 31.5 m × 45 m during 2013–2014. Results We found that the effects of increasing harvesting intensity on plant diversity changed from negative to positive (and from nonlinear to more linear responses) with increasing site productivity. Harvesting intensity showed contrasting effects on variables related to fire protection ecosystem service, since it reduced fuel amount (potentially reducing fire spread) but also reduced live fuel moisture content (potentially increasing flammability) at the three sites. Two variables related to soil formation and protection ES, leaf litter cover and aerial soil cover, decreased with harvesting intensity at the three sites. Conclusions We conclude that shrubland management for firewood production may enhance biodiversity without compromising certain important ES. The intensity of harvesting should be determined according to site conditions and forecasted impacts on biodiversity, fire and soil formation and protection.